The Ability to Manage Leucorrhea in Adolescents through Vulva Hygiene - Widiastuti, Yuni Puji; Iqomh, Muhammad Khabib Burhanudin; Nazza, Fisca Benny; Musyarofah, Siti; Rakhmawati, Julia (Global Health Science Group, 2024)
Reproductive health is a crucial health issue especially for teenagers who have no experience. Some reproductive health issues that arise include vaginal discharge. We can prevent this through good personal hygiene, especially vulva hygiene. This is an effort made by individuals to maintain personal hygiene. Some teenagers do not do vulva hygiene and the behavior in doing vulva hygiene is still not in accordance with what it should be. They clean the genitalia from back to front. The prevalence of vaginal discharge management in teenagers in the Islamic boarding school environment shows (51.3%) do not do vaginal discharge management properly. Improper vulva hygiene behavior will cause infectious diseases such as candidiasis, bacterial vaginosis, vaginal discharge, cervicitis and dermatitis. The Objective of this research is to determine the ability to manage vaginal discharge or leucorrhea in adolescents. Research design using descriptive with crossectional approach. The sample was 52 respondents with total sampling technique. Data was taken using questionnaire. Data analysis used descriptive statistics. The vulva hygiene skills of adolescent girls are mostly in the sufficient category, namely 48 respondents (92.3%), and in the inadequate category, namely 4 respondents (7.7%). The ability to manage vaginal discharge in adolescents using vulva hygiene is still not appropriate, therefore it is important to educate adolescents about managing vaginal discharge so that adolescents have the correct knowledge and are able to maintain reproductive health from an early age.